The Arrival of Robotics in Spine Surgery: A Review of the Literature - Ghasem, Alexander; Sharma, Akhil; Greif, Dylan N; Alam, Milad; Maaieh, Motasem Al (Spine (Philadelphia, Pa. 1976), 2018)
Systematic review. The authors aim to review comparative outcome measures between robotic and free-hand spine surgical procedures including: accuracy of spinal instrumentation, radiation exposure, operative time, hospital stay, and complication rates. Misplacement of pedicle screws in conventional open as well as minimally invasive surgical procedures has prompted the need for innovation and allowed the emergence of robotics in spine surgery. Before incorporation of robotic surgery in routine practice, demonstration of improved instrumentation accuracy, operative efficiency, and patient safety are required. A systematic search of the PubMed, OVID-MEDLINE, and Cochrane databases was performed for articles relevant to robotic assistance of pedicle screw placement. Inclusion criteria were constituted by English written randomized control trials, prospective and retrospective cohort studies involving robotic instrumentation in the spine. Following abstract, title, and full-text review, 32 articles were selected for study inclusion. Intrapedicular accuracy in screw placement and subsequent complications were at least comparable if not superior in the robotic surgery cohort. There is evidence supporting that total operative time is prolonged in robot-assisted surgery compared to conventional free-hand. Radiation exposure appeared to be variable between studies; radiation time did decrease in the robot arm as the total number of robotic cases ascended, suggesting a learning curve effect. Multilevel procedures appeared to tend toward earlier discharge in patients undergoing robotic spine surgery. The implementation of robotic technology for pedicle screw placement yields an acceptable level of accuracy on a highly consistent basis. Surgeons should remain vigilant about confirmation of robotic-assisted screw trajectory, as drilling pathways have been shown to be altered by soft tissue pressures, forceful surgical application, and bony surface skiving. However, the effective consequence of robot-assistance on radiation exposure, length of stay, and operative time remains unclear and requires meticulous examination in future studies. 4.